A Review of Cyberloafing Predictors in Literature - Huda M. Mashal (Sustainable Business and Society in Emerging Economies, 2020)
Surfing the Internet for personal purposes during working hours is known as cyberloafing. Employers consider cyberloafing as a counterproductive behavior that causes productivity losses. Researchers, however, have demonstrated to find cyberloafing beneficial for the employees' social and emotional needs. It is essential to investigate the causes of cyberloafing to predict the behavior and recommend the appropriate workplace Internet use policies in favor of employee productivity. This paper will provide the main tested cyberloafing predictors in the literature. This paper will provide academic information necessary for establishing future researches on cyberloafing.